Trend of Oil Prices, Gold, GCC Stocks Market during Covid-19 Pandemic: A Wavelet Approach - Rafiuddin, Aqila; Daffodils, Jennifer; Gaytan, Jesus Cuauhtemoc Tellez; Sisodia, Gyanendra Singh (International Journal of Energy Economics and Policy, 2021)
This paper analyzed the co-movement among the stock indices of GCC members like Abudhabi, Bahrain, Oman, Saudi Arabia, Qatar and global oil prices as indicated by Brent, WTI. Gold, S&P 500 index and Dow Jones index has also been taken into account. Daily prices from January 2, 2020 up to September 30, 2020 were used for the analysis. In order to analyze the co-movement among the above mentioned indices in time frequency space wavelet transform approach has been used. The techniques employed in the study include wavelet correlation and wavelet coherence approach. The findings of this empirical study suggests that though there was no much interconnectedness among the above mentioned factors in the short run, the impact of the global pandemic crisis that got added to the oil price shock could be seen in the medium and long run. The study suggests that investors need to be cautious of their investment decisions with respect to the time horizon as these markets show significant co-movement in the long run when hit by global crisis. Keywords: Oil Prices, GCC Stock Indices, Co-movement, Wavelet Analysis JEL Classifications: G01, G15,C32 DOI: https://doi.org/10.32479/ijeep.11365